Divje babe I Paleolitsko najdišče mlajšega pleistocena v Sloveniji (1. del: Geologija in paleontologija) = Upper Pleistocene palaeolithic site in Slovenia (Part 1: Geology and Palaeontology) - Turk, Ivan (Opera Instituti Archaeologici Sloveniae, 2007)
In the first part of the Divje babe I monograph, data from the field of the natural sciences is presented, analysed and interpreted. This is primarily stratigraphic, sedimentological and chronological data and data on the remains of flora and fauna. The latter includes detailed analysis of charcoal from a number of hearths and the remains small and large mammals, with a stress on cave bear. The series of absolute ESR datings and the climatogram of the site should be highlighted in particular, which shows the course of temperature and humidity by layers in the chronozone of the Early and Middle Würm or oxygen isotope stages OIS 5 and OIS 3. The remains of flora and fauna from OIS 3 in particular are analysed, which enables new insight into palaeo-environmental and climatic conditions of this poorly known chronological segment in Slovenia and neighbouring regions. Archaeological finds, including Mousterian bone artefacts, will be presented in the planned second part of the monograph.